2018
DOI: 10.31234/osf.io/xp2gk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social perspective taking is associated with self-reported prosocial behavior and regional cortical thickness across adolescence

Abstract: Basic perspective taking and mentalising abilities develop in childhood, but recent studies indicate that the use of social perspective taking to guide decisions and actions has a prolonged development that continues throughout adolescence. Here, we aimed to replicate this research and investigate the hypotheses that individual differences in social perspective taking in adolescence are associated with real-life prosocial and antisocial behavior and differences in brain structure. We employed an experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Consistent with prior studies, we found that higher levels of intention to comfort and social perspective taking at the final wave were uniquely related to more prosocial behavior, but these measures were not related to rebellious behavior. The relations among empathic tendencies, perspective taking, and prosocial behaviors have been well documented (Eisenberg, ; Overgaauw et al, ; Tamnes et al, ), and previous studies also reported relations between emotionality and prosocial behavior (Eisenberg et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with prior studies, we found that higher levels of intention to comfort and social perspective taking at the final wave were uniquely related to more prosocial behavior, but these measures were not related to rebellious behavior. The relations among empathic tendencies, perspective taking, and prosocial behaviors have been well documented (Eisenberg, ; Overgaauw et al, ; Tamnes et al, ), and previous studies also reported relations between emotionality and prosocial behavior (Eisenberg et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…This process results in more fine‐tuned brain regions that yield more efficient cognitive and social processing and improved performance with age (Blakemore, ). Indeed, structural brain development, capturing the most consistent within‐individual patterns of change, has been associated with a number of developmental outcomes such as identity formation and social functioning (Becht et al, ; Blakemore & Mills, ; Tamnes et al, ), yet how structural development relates to prosocial and/or risk‐taking behaviors is less well known.…”
Section: The Current Studymentioning
confidence: 99%
“…the ability to attribute thoughts, perspectives, opinions, and emotions to others, contributes to the emergence of pragmatic competence during development [4,37,64]. ToM is still developing in adolescence; adolescents make more errors and use perspective taking less frequently than adults when performing tasks that require representing other people's mental states [19,29,57,59].…”
Section: Introductionmentioning
confidence: 99%
“…42 Performers will vary in how sensitive they are to audience reactions. Adolescence is associated with increasing awareness of others' perspectives, 43,44 and increased susceptibility to peer influence 25,26 and sensitivity to peer exclusion. 28 In the course of adolescence, students tend to become more sensitive to audience reactions, from teachers but especially from other students.…”
Section: Audience Reaction and Its Impact On Performersmentioning
confidence: 99%